Pengaruh Lingkungan Kerja dan Kompensasi Terhadap Kinerja Karyawan dengan Kepuasan Kerja Sebagai Variabel Antara di PT Sinar Surya Matahari Motor - Yohana Pangestu; Ignatius Ario Sumbogo (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this study is to find out whether there is an influence of the work environment and compensation on employee performance with job satisfaction as a variable between pt Sinar Surya Matahari Motor. This study uses validity tests, reliability tests, multiple linear regression tests, and path analysis tests with the help of the SPSS version 20 program. Samples were taken by 110 respondents. The research uses quantitative approach with purposive sampling technique method. Data collection is done by disseminating questionnaires using the Likert scale to measure each statement. The results showed that there was a separate positive and significant influence between the work environment and compensation for the performance of employees directly. While the significance of the influence of the work environment and compensation through job satisfaction is not greater than the direct influence.